Agregação de fatores de risco para diabetes mellitus gestacional e a macrossomia fetal em participantes do Projeto Viver - Oliveira, Gabriela (2023)
The existence of risk factors, modifiable or not, in the lives of pregnant women favors the development of diseases and the presence of more than one risk factor tends to potentiate its effects. This study aimed to analyze the aggregation of risk factors for the development of gestational diabetes mellitus and fetal macrosomia in the participants of Projeto Viver. This is an observational, cross-sectional study, conducted from data collected by Projeto Viver, which was a multicenter, longitudinal and state study with puerperal women and their newborns selected from three maternity hospitals located in the Metropolitan region and North of Espírito Santo. Data collection was carried out between August 2019 and March 2020. First, the need to carry out a systematic review was identified to understand more about the population of interest. The sample for article 2 consisted of 2,488 women who had filled in information about the variables of interest for each study and aimed to analyze the aggregation of risk factors (advanced maternal age, family history of diabetes mellitus, overweight and multiparity). for gestational diabetes mellitus. The prevalence of risk factors, their confidence intervals and distributions according to sociodemographic aspects were calculated, such as: race (white or non-white), years of education (≤8 years or >8 years), currently working (Yes or No) , hospital assistance (Philanthropic ME, Philanthropic NO and Private) and index of goods according to the classification of the Brazilian Association of Population Studies (ABEP) (A and B; C; D and E). Aggregation was evaluated based on the ratio of the prevalence of observed factors to the expected prevalence. The aggregation of the four analyzed factors was verified (O/E=2). In the aggregation of the three risk factors, the most frequent was a family history of diabetes, advanced maternal age and multiparity (O/E=2.8). In the third article, in addition to the aggregation analysis, the Odds Ratio of prevalence was also calculated (ORP) to identify the aggregation of two factors, regardless of the exposure of the other two factors, and aimed to analyze the aggregation of risk factors (gestational diabetes, advanced maternal age, overweight and multiparity) for fetal macrosomia. The sample consisted of 2,488 women and the aggregation of the four risk factors (O/E=3.9) was identified. As for the Odds Ratio of prevalence, there was a greater association between gestational diabetes and advanced maternal age (ORP = 2.76), especially in those who do not work. Although the synergistic effect of risk factors is already known, few studies have explored these relationships, especially in this population. Strategies focused on the health and lifestyle pattern of the female population can contribute to controlling the incidence of gestational diabetes and fetal macrosomia. Understanding the real situation of puerperal women regarding the aggregation of risk factors is an important step to encourage prevention actions and strategies.